Strong Photocurrent from Solution‐Processed Ruddlesden–Popper 2D Perovskite–MoS2 Hybrid Heterojunctions - Rashid M. Ansari; Akshaykumar D. Salunke; Mohammad Rahil; Shahab Ahmad (Advanced Materials Interfaces, 2023)
Abstract This study reports overall improvement in structural, morphological, and optoelectronic properties of Ruddlesden–Popper (RP) perovskites of type (BA)2(MA)n−1PbnI3n+1 by forming their bulk heterojunction hybrids with few‐layer MoS2 nanoflakes. RP perovskite–MoS2 hybrid thin films have shown significantly improved packing and crystallinity compared to pristine perovskites. The presence of MoS2 at RP perovskite interface has improved the quantum confinement effects and transport of photogenerated charge carriers from perovskite to MoS2, due to suitable conduction band of MoS2 and more number of decay channels. The optoelectronic properties of RP perovskite–MoS2 hybrids are studied for various MoS2 concentrations (4.2–25.6 × 10−3 m) and at optimum concentration (12.8 × 10−3 m) the photodetectors (n = 2, 4) have shown strong, sharp, and highly stable photocurrent response. At 0.0 V bias, the RP perovskite (n = 4) and MoS2 (12.8 × 10−3 m) hybrid‐based photodetectors, prepared without any encapsulation, have shown strong photocurrent density of ≈9.8 µA cm−2 under 1 sun illumination, which is ≈17 times higher compared to the pristine RP perovskites‐based photodetector (0.6 µA cm−2). Further transient photocurrent, performed over 200 cycles for hybrid (n = 4+MoS2) thin film photodetector under laser (λex ≈ 405 nm, ≈630 mW cm−2) illumination and ambient air conditions has shown highly stable photocurrent with only ≈9.6% reduction in the peak photocurrent density.